Characteristics of Zika virus infection among international travelers: A prospective study from a Spanish referral unit. Issue 33 (January 2020) - ,; García, Julio; Martín-Boado, Elena; Martínez-Sánchez, Nuria; Rodríguez, Roberto; Herrero, Beatriz; López, Francisco; Bartha, Jose Luis; Elorza, Maria Dolores; Lafuente, Marta Cabrera; Hortelano, Milagros García; Crespillo-Andújar, Clara; et al.
Abstract: Background: From the first Zika virus (ZIKV) description, it has progressively widespread worldwide. We analyzed demographic, clinical, microbiologic and travel-related characteristic from returned patients from a ZIKV endemic country in a referral Tropical Medicine Unit. Method: A prospective cohort study performed in a Spanish referral center with the aim of determining the significant factors associated with confirmed Zika virus (ZIKV) infection. Results: 817 patients, (56% women, median age 36 [IQR, Interquartile Range : 32–42]) were enrolled. Most had returned from Latin America (n = 486; 59.4%), travelled for tourism (n = 404; 49.4%) and stayed a median of 18 days (IQR: 10–30). 602 (73.6%) presented symptoms, but only 25 (4%) were finally diagnosed with confirmed ZIKV infection (including two pregnant women, without adverse fetal outcomes), 88% (n:22) presented with fever and 92% (n:23) with rash. 56% (n:14) arthralgia and/or myalgia and 28% (n:7) conjunctivitis. The presence of conjunctivitis, fever and rash were associated with an 8.9 (95% CI: 2.2–34.9), 6.4 (95% CI: 1.2–33.3) and 72.3 (95% CI: 9.2–563.5) times greater probability of confirmed ZIKV infection, respectively. Conclusion: Travel characteristics and clinical presentation may help clinicians to optimize requests for microbiological testing. Diagnosis of arboviriasis in travellers arriving form endemic areas remains a challenge for clinicians, but must be detected for the possible transmission outside endemic areas, where the vector is present.